Mosaic distal 9p deletion or 46,XY,del(9)(p23)/46,XY at amniocentesis in a pregnancy associated with perinatal progressive decrease of the aneuploid cell line and a favorable fetal outcome - Chih-Ping Chen; Fang-Tzu Wu; Yen-Ting Pan; Peih-Shan Wu; Chen-Chi Lee; Wen-Lin Chen; Chien-Ling Chiu; Wayseen Wang (Elsevier, 2024)
Objective: We present mosaic distal 9p deletion at prenatal diagnosis in a pregnancy associated with a favorable fetal outcome. Case report: A 34-year-old, primigravid woman underwent amniocentesis at 17 weeks of gestation because of advanced maternal age. Amniocentesis revealed a karyotype of 46,XY, del(9)(p23)[8]/46,XY[17]. Simultaneous array comparative genomic hybridization (aCGH) analysis on the DNA extracted from uncultured amniocytes showed 43% mosaicism for the 9p24.3p23 deletion. Prenatal ultrasound suspected hypospadias and echogenic bowel. At 23 weeks of gestation, she was referred for genetic counseling, and repeat amniocentesis revealed a karyotype of 46,XY,del(9)(p23)[10]/46,XY[10]. The parental karyotypes were normal. Molecular genetic analysis on uncultured amniocytes revealed no uniparental disomy (UPD) 9 by quantitative fluorescence polymerase chain reaction (QF-PCR) and arr 9p24.3p23 × 1.55 (40%-50% mosaicism) by aCGH. At 27 weeks of gestation, she underwent the third amniocentesis which revealed a karyotype of 46,XY,del(9)(p23)[6]/46,XY[14]. Simultaneous aCGH analysis on the DNA extracted from uncultured amniocytes revealed the result of arr 9p24.3p23 (35% mosaicism). Prenatal ultrasound was normal. She was advised to continue the pregnancy, and a 3020-g phenotypically normal male baby was delivered at 41 weeks of gestation. At birth, the karyotypes of cord blood, umbilical cord and placenta were 46,XY,del(9)(p23)[7]/46,XY[37], 46,XY,del(9)(p23)[17]/46,XY[23] and 46,XY in 40/40 cells, respectively. When follow-up at age three months, the neonate was normal in phenotype and development. The peripheral blood had a karyotype of 46,XY,del(9)(p23)[3]/46,XY[37], and interphase fluorescence in situ hybridization (FISH) analysis on buccal mucosal cells showed 13% (13/102 cells) mosaicism for the distal 9p deletion. Conclusion: Mosaic distal 9p deletion with a normal cell line at prenatal diagnosis can be associated with a favorable fetal outcome and perinatal progressive decrease of the aneuploid cell line.